Teste e avaliação do Modelo sMOOC como suporte ao desenvolvimento de sMOOCs pelo professor em educação superior no Brasil - Souza, Flávio Lemos de (2022)
During the last few years it has been observed a very rapid growth in the use of MOOCs in higher education by Universities in Europe and elsewhere. The educational community has come to a predominant view agreeing on the lack of quality of many of those courses with regard to consolidated pedagogical principles, eLearning theories, and good practices. Investments have been made both at national and international level, in particular with regard to the issue of quality and formal accreditation in the use of MOOCs granting a pathway to higher education. In order to achieve quality, frameworks have been developed to support the creation of better quality and more effective MOOCs, but there seems to be a lot of work still to be done. This paper aims to offer some contributions to the development of frameworks for better quality and more effective MOOCs design. Two empirical studies have been carried out addressing a MOOC funded by the European Commission, whose main objective was to introduce school teachers the some internet based pedagogical experiences which could be applied to their teaching as blended practice. The first study consisted of an expert analysis where the researcher took part as a participant/learner in the MOOC. The second consisted of an empirical evaluation study of a group of brazilian school teachers taking part as learners in the MOOC. Errors and difficulties by the participants were identified during the course and analysed as a means to recommend improvements to the MOOC design, as well as to bring about relevant information to the development of frameworks to support better quality and more effective MOOCs design. The results have led to the observation that although the particular MOOC under analysis has shown compliance to most of the high level and theoretical pedagogical MOOCs principles, some important low level and practical instructional design as well the system usability have not been received the attention as required. This seems to have led to a high drop rate. In conclusion, this paper supports the view that frameworks conceived as a tool to support MOOC design to meet quality and effective learning experience, should include not only high level theories and pedagogical principles (as most of they currently do), but also integrate the low level instructional design as well as the user centred guidance.